2010
DOI: 10.1002/ana.21994
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic sensitization transforms localized pain into widespread allodynia

Abstract: Objective-Focal somatic pain can evolve into widespread hypersensitivity to non-painful and painful skin stimuli (allodynia and hyperalgesia, respectively). We hypothesized that transformation of headache into whole-body allodynia/hyperalgesia during a migraine attack is mediated by sensitization of thalamic neurons that process converging sensory impulses from the cranial meninges and extracephalic skin.Methods-Extracephalic allodynia was assessed using single unit recording of thalamic trigeminovascular neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
290
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(316 citation statements)
references
References 49 publications
13
290
1
2
Order By: Relevance
“…147 In another fMRI study, thalamic sensitization cor related with widespread mechanical allodynia during the migraine attack. 148 Moreover, in a diffusion tensor MRI study, our research group found dynamic ictal and inter ictal microstructural variations in the thalamus that were related to the time since the last migraine attack, and seemed to mimic the cyclic neurophysiological changes described above. 149 Collectively, these observations suggest that a search for optimal methods of influencing the cortical tem poral processing of exogenous stimuli that can trigger a migraine attack, or methods for modulating endo genous trigeminal noxious inputs that lead to central sensitization and eventually chronic headache, could result in novel interventions for migraine prevention.…”
Section: Prospects For Clinical Researchmentioning
confidence: 75%
“…147 In another fMRI study, thalamic sensitization cor related with widespread mechanical allodynia during the migraine attack. 148 Moreover, in a diffusion tensor MRI study, our research group found dynamic ictal and inter ictal microstructural variations in the thalamus that were related to the time since the last migraine attack, and seemed to mimic the cyclic neurophysiological changes described above. 149 Collectively, these observations suggest that a search for optimal methods of influencing the cortical tem poral processing of exogenous stimuli that can trigger a migraine attack, or methods for modulating endo genous trigeminal noxious inputs that lead to central sensitization and eventually chronic headache, could result in novel interventions for migraine prevention.…”
Section: Prospects For Clinical Researchmentioning
confidence: 75%
“…These functional characteristics appeared after mechanical or thermal stimulation of extracephalic skin areas [34,7]. The same group, through fMRI studies during migraine attack in patients with whole-body allodynia, described a specific thalamic activation after brush and heat stimuli [38].…”
Section: Sensitizationmentioning
confidence: 89%
“…Development of pulsatility in the initial phase of migraine is mediated by sensitization of peripheral neurons of the trigeminal vascular system and allodynia cutaneous later during acute migraine is propelled by sensitization central neurons [32]. We have found the lowest pain thresholds in patients with longer duration of headache (over 10 years), probably by constant inflammatory state that sensitizes cranial nociceptors, leading to decreased activation of its receptors.…”
Section: /6mentioning
confidence: 59%